Aminolysis of bis[bis(trimethylsilyl)amido]-manganese, -iron, and -cobalt for the synthesis of mono- and bis-silylene complexes. Issue 36 (28th August 2020) - He, Zhiyuan; Xue, Xiaolian; Liu, Yilan; Yu, Na; Krogman, Jeremy P.
Abstract : Mono- and bis-silylene metal complexes may be synthesized in high yield from MN(SiMe3 )2 2 and PhC(N t Bu)2 SiHCl2 . Abstract : We report a method for the synthesis of amidinate stabilized silylene (NHSi) metal–halide complexes from MN(SiMe3 )2 2 (M = Mn, Fe, Co). The reported reactions can be used to make mono-silylene or bis-silylene complexes and the resulting products can be easily controlled by the reaction stoichiometry. Additionally, we apply this new synthetic protocol for the synthesis of a bis-iron complex derived from a bis-amidinate ligand having a terphenyl backbone.